EFEKTIVITAS PROGRAM PERTUKARAN MAHASISWA DALAM MENINGKATKAN NILAI MULTIKULTURAL PADA MAHASISWA PENDIDIKAN OLAHRAGA - Al Muhaimin Septian; Ugi Nugraha; Mohd. Adrizal (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study aims to describe the effectiveness of student exchange programs in forming and enhancing multicultural values among sports education students. The approach used is qualitative with a case study type. The informants in this study were four sports education students who participated in the Merdeka Student Exchange Program (PMM) from various regions and participated in an exchange program at PGRI Semarang University. Data collection techniques were conducted through in-depth interviews online using Zoom Meeting. The research results show that the student exchange program is effective in fostering understanding of cultural diversity, strengthening tolerance and empathy attitudes, improving adaptation abilities, and strengthening cross-cultural cooperation and communication among sports education students. Students not only understand multicultural values theoretically but also internalize them through real experiences during the program. This experience shapes inclusive, tolerant, and open characters to differences. Thus, it is concluded that this student exchange program is proven effective in forming multicultural values that are important for sports education students in diverse Indonesia.